A review article on brodalumab in the treatment of moderate-to-severe plaque psoriasis. (September 2017) - Roostaeyan, Omid; Kivelevitch, Dario; Menter, Alan
Psoriasis is a chronic immune-mediated skin disorder affecting approximately 2–3% of the worldwide population. Recent advances in our understanding of the immunopathogenesis of psoriasis have resulted in novel therapeutic agents. IL-17, a pro-inflammatory cytokine, plays a pivotal role in psoriasis. Therapeutic agents targeting this cytokine have shown clinical effectiveness in the treatment of moderate-to-severe plaque psoriasis. Brodalumab, a human antibody against IL-17 receptor A, has been approved by the US FDA in February 2017, by the Japanese Pharmaceuticals and Medical Devices Agency in July 2016 and by the EMA in July 2017 for the treatment of moderate-to-severe psoriasis. This article reviews the published data relating to brodalumab for the treatment of moderate-to-severe plaque psoriasis.